Functional assembly of surface microbiota of Ulva fasciata improves nutrient absorption efficiency and growth - Wang, Han; Li, De-hua; Wang, Jing-ru; Wang, Rong; Liang, Chang-li; Hu, Zhong; Liu, Jun-he (Frontiers in Microbiology, 2024)
Macroalgae growth depends on biologically available nitrogen, such as ammonium and nitrate, making nitrogen the most common growth-limiting factor for macroalgae. However, the role of surface microorganisms in promoting nitrogen transformation and improving nitrogen utilization by macroalgae remains unclear. In this study, 228 bacterial strains were isolated from the surface of U. fasciata, and high-throughput sequencing revealed significant shifts in the composition of surface bacterial communities under different nitrogen concentrations. Key bacterial families such as Rhodobacteraceae and Flavobacteriaceae were identified as essential for nitrogen cycling. Network analysis indicated that Rhodobacteraceae and Flavobacteriaceae were central nodes in microbial interactions. A synthetic microbial community (SynCom2), comprising four strains, significantly increased the biomass, nitrogen, and phosphorus acquisition of U. fasciata, with soluble sugar, protein, and Chlorophyll a level increasing by 23.9–49.2%. Quantitative reverse transcription polymerase chain reaction (RT-qPCR) analysis revealed that compared to untreated control plants, SynCom2 enhanced the expression of key genes associated with photosynthesis (rbcL, 1.04-fold), lipid biosynthesis (accD, 11.21-fold), and growth hormone precursor pathways (wrkY, 9.54-fold). These findings suggest that SynCom2 promotes U. fasciata growth by improving nutrient acquisition and activating growth-related genes.